PENGARUH KELELAHAN EMOSIONAL TERHADAP MOTIVASI KERJA DAN KEPUASAN KERJA KARYAWAN PT PELINDO IV (PERSERO) CABANG AMBON - Kowey, Wylda Olivia (Fakultas Ekonomi Universitas Wisnuwardhana, 2016)
This study aimed to examine the effect of emotionalexhaustion on work motivation and job satisfaction of employeesof PT Pelindo (Persero) Ambon Branch. Hypothesis testing isdone using Path Analysis. The results showed that emotionalexhaustion and significant negative effect on work motivation ofemployees, emotional exhaustion has negative effect on jobsatisfaction, while working motivation positive and significantimpact to the satisfaction, then emotional exhaustion is also has anegative effect on job satisfaction through work motivation. Thestudy provides an understanding that if the management of PTPelindo IV (Persero) Ambon Branch want to increase theiremployees motivation and job satisfaction then one importanteffort needs to be made to reduce their levels of emotionalexhaustion. So, a refreshing programe can be done on aregularly.Key word : Emotional exhaustion, work motivation, worksatisfactionAbstrak. Penelitian